ANTIPSYCHOTIC TREATMENT AND WEIGHT GAIN: DOES RISPERIDONE BEHAVE DIFFERENTLY IN PAKISTANI PSYCHIATRIC PATIENTS? - Iqbal, Saleem Perwaiz; Khan, Rashid AM; Ahmer, Syed (Journal of Ayub Medical College Abbottabad, 2011)
Background: Studies from the Western world have shown that antipsychotic medications in psychiatric patients result in weight gain and other metabolic diseases. This study was undertaken to investigate whether any one of the five most commonly prescribed antipsychotics, (risperidone, olanzepine, trifluoperazine, quetiapine and haloperidol) could behave differently in terms of causing weight gain among patients attending the psychiatric outpatient clinics in a tertiary care hospital in Karachi, Pakistan. Methods: For this retrospective cohort study, data were collected from outpatient records of the Aga Khan University Hospital, from 2003 to 2007. Demographic and clinical data were analysed. Repeated measures ANOVA, using a linear mixed model approach was used to assess weight gain over time due to the use of antipsychotic medications. Results: A total of 124 subject records (68 males and 56 females) were evaluated. One-way ANOVA revealed that the groups being prescribed with antipsychotics were comparable with respect to age, duration of treatment and weight measurements. Frequencies were calculated which showed that weight increases significantly over time with respect to the prescribed antipsychotic medications, except for risperidone. Repeated measures ANOVA using the linear mixed model approach showed that the serial weight measurements were significantly different across the follow up times (p<0.05). Conclusion: Four of the commonly prescribed antipsychotic drugs do result in an increase in weight; however risperidone has no such effect, making it an option in treating psychiatric disorders without worrying for any gain in weight. In view of the increased prevalence of obesity and other metabolic diseases, measures should be taken towards careful prescription of antipsychotic medications. Keywords: Schizophrenia depression weight gain obesity antipsychotics risperidone